2023
DOI: 10.3390/molecules28134957
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Value of Solanum Steroidal (Glyco)Alkaloids: A 10-Year Comprehensive Review

Abstract: Steroidal (glycol)alkaloids S(G)As are secondary metabolites made of a nitrogen-containing steroidal skeleton linked to a (poly)saccharide, naturally occurring in the members of the Solanaceae and Liliaceae plant families. The genus Solanum is familiar to all of us as a food source (tomato, potato, eggplant), but a few populations have also made it part of their ethnobotany for their medicinal properties. The recent development of the isolation, purification and analysis techniques have shed light on the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 190 publications
0
5
0
Order By: Relevance
“…Plants have emerged as an alternative source of enzymes as they do not manifest pathogenicity and can be used as either crude extracts or in purified form to treat or use against many human diseases. , There are many purified compounds from plants such as taxol and vinblastine that are being used as chemotherapeutic drugs to treat many cancers . The edible fruit of Solanum lycopersicum has a wide range of biological effects and has been reported to have many health benefits. Tomatoes help reduce the risk of cardiovascular diseases, atopic dermatitis, liver inflammatory disease, and inflammatory bowel diseases . The anticancer properties of l -asparaginase are well documented, particularly against ALL .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants have emerged as an alternative source of enzymes as they do not manifest pathogenicity and can be used as either crude extracts or in purified form to treat or use against many human diseases. , There are many purified compounds from plants such as taxol and vinblastine that are being used as chemotherapeutic drugs to treat many cancers . The edible fruit of Solanum lycopersicum has a wide range of biological effects and has been reported to have many health benefits. Tomatoes help reduce the risk of cardiovascular diseases, atopic dermatitis, liver inflammatory disease, and inflammatory bowel diseases . The anticancer properties of l -asparaginase are well documented, particularly against ALL .…”
Section: Resultsmentioning
confidence: 99%
“… 41 The edible fruit of Solanum lycopersicum has a wide range of biological effects and has been reported to have many health benefits. 42 44 Tomatoes help reduce the risk of cardiovascular diseases, atopic dermatitis, liver inflammatory disease, and inflammatory bowel diseases. 45 The anticancer properties of l -asparaginase are well documented, particularly against ALL.…”
Section: Resultsmentioning
confidence: 99%
“…Solacauline and demissine are steroidal alkaloids, a class of compounds largely unique to Solanum and Liliaceae , of which approximately 300 structures have been reported ( Morillo et al., 2020 ). Steroidal alkaloids are nitrogenous sterols (a solanidane group) that are usually conjugated to 2-4 saccharides, with the saccharide component being critical to their bioactivity ( Delbrouck et al., 2023 ). These compounds provide protection by disrupting cell membranes of pests and pathogens ( Niño et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…205–209 They are classified into solanidane and spirosolane, based on their skeleton derived from the cholesterol side chain. 210,211 Recently, Mizutani's, Aharoni's, and other research groups identified the biosynthetic pathway of SGAs. 184,212–218 As shown in Fig.…”
Section: Novel Biosynthetic Pathwaysmentioning
confidence: 99%